2014
DOI: 10.3109/02688697.2014.976174
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tadalafil—Type-V phosphodiesterase enzyme inhibitor—On rats with spinal trauma

Abstract: In this research, the effect of tadalafil, a selective inhibitor of cyclic guanosine monophosphate-specific phosphodiesterase type 5, on rats with spinal trauma was evaluated. The evaluation consisted of neurological examination and biochemical parameters. Twenty healthy male Wistar albino rats were used in this study. They were separated into three groups: tadalafil-receiving (TD) group (n=7), laminectomy and trauma (LT) group (n=7), and just laminectomy group (n=6). The TD group received daily dose of tadala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…Finally, our results clearly showed that trauma increased the levels of MDA, TNF-α, IL-1β and IL-6 in the spinal cord of rats at 24 hours after injury and these results are similar to those in the literature (3,5,14,16,17). AA administration just after the trauma inhibited post-traumatic inflammation and overproduction of ROS and reduced MDA and pro-inflammatory cytokine (TNF-α, IL-1β) levels.…”
Section: █ Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Finally, our results clearly showed that trauma increased the levels of MDA, TNF-α, IL-1β and IL-6 in the spinal cord of rats at 24 hours after injury and these results are similar to those in the literature (3,5,14,16,17). AA administration just after the trauma inhibited post-traumatic inflammation and overproduction of ROS and reduced MDA and pro-inflammatory cytokine (TNF-α, IL-1β) levels.…”
Section: █ Discussionsupporting
confidence: 81%
“…If the redox balance between reactive oxygen species and cellular free radical scavengers is disturbed, there will be an energy failure in the cell that causes apoptosis and cell death in neurological disorders such as stroke, Parkinson disease, Alzheimer disease and neurotrauma. Our results showed that spinal cord trauma caused a significant increase in the MDA level during the secondary injury with respect to the only laminectomy group as documented in the literature (3,15,16). AA administration just after the SCI reduced the MDA level compared with the laminectomy trauma group.…”
Section: Interleukin 1βsupporting
confidence: 72%
“…One found that tadalafil significantly improved upper and lower limb locomotion and reduced inflammatory biomarkers, such as interleukin 6, tumor necrosis factor α, and malondialdehyde after spinal cord contusion when compared with the control group. 17 Secondary injury processes can be mediated by lipid peroxidation by free radicals, accumulation of intracellular Ca 2+ , and inflammation. It is possible that tadalafil can address all three by reducing malondialdehyde (by-product of lipid peroxidation) and decreasing Ca 2+ influx through cyclic guanosine monophosphate, which can also attenuate the inflammatory process.…”
Section: Discussionmentioning
confidence: 99%
“…The thorax was dissected and the left ventricle was cannulated to perform intracardiac perfusion with 100-300 ml phosphate buffered saline (pH 7.4) and 100 ml paraformaldehyde (4% in 0.1 mol phosphate buffered saline) (19). All hemorrhagic components of the spinal cord tissue were removed with NaCl 0.9% solution.…”
Section: Tissue Preparationmentioning
confidence: 99%